(untitled) (Bangladesh Journal of Scientific Research, 2012)
Key words: Outliers; robustness; iterative algoritm; computational efficiency; median product DOI: http://dx.doi.org/10.3329/bjsr.v24i2.10766 Bangladesh J. Sci. Res. 24(2):97-106, 2011 (December)